Epidemiological assessment of the health and nutrition of Ethiopian refugees in emergency camps in Sudan, 1985. - Shears, P (1987)
The findings from epidemiological data that were collected from emergency camps for Ethiopian refugees during a mass influx of refugees into Eastern Sudan in 1985 are presented. An overall mortality of 8.9 per 10,000 a day was recorded during February 1985, and in children under 5 years of age the rate was 22 per 10,000 a day. The estimated prevalence of malnutrition (calculated as less than 80% of the reference weight for height) ranged from 32% to 52% among children of preschool age. The principal causes of morbidity and mortality were measles, diarrhoea and dysentery, respiratory infections, and malaria. The findings suggest that malnutrition and disease increased in these refugees after they arrived in the camps. Epidemiological assessment is essential to help to maintain the health and nutrition of refugees in emergency camps.